PENGARUH PENGELUARAN PEMERINTAH DI SEKTOR PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Siringoringo, Maris Verawati; Purwono, Rudi (2021)
This study investigates the effect of education expenditure on economic growth in Indonesia. Gross Domestic Product (GDP) is used as dependent variable on the explanatory variables of government expenditure on education. Time series data are from 1988 to 2019. This study adopts the Autoregresive Distributed Lag (ARDL) method. The results showed that education expenditure in Indonesia had a positive effect on economic growth positively. A greater allocation of resources on education expenses could make the Indonesia economy more dynamic.